A novel approach for mapping WRB soil units – A methodology for a global SOTER coverage - Dobos, Endre; Vadnai, Péter; Kovács, Károly; Láng, Vince; Fuchs, Márta; Michéli, Erika (Hungarian Geographical Bulletin, 2019)
Traditional soil maps present soil information in the form of categorical classes of soil types classified on the appropriate level of the applied classification system corresponding to the scale. Soil complexes and associations have been used to describe polygons. This kind of data structure is useful to characterise an area by explaining its soil resources. However, it is difficult to convert these complex categorical units into a simple digital variable, the usage of this kind of data in a digital environment is limited. Users often need single properties instead of the complex classes. Additionally, the problem becomes more complicated when soil information of different origin, based on different classification systems has to be integrated into a common, harmonised database. The presented methodology is part of the efforts to develop a global SOTER (World Soil and Terrain database) coverage and contribute to the global soil observing s as part of the Global Earth Observing System of Systems (GEOSS). The aim is to determine and map the relevant soil properties, horizons and materials following the diagnostic concepts of the World Reference Base (WRB) for soil resources andderive the occurrence probability of soil classes (WRB reference soil groups) of certain spots with the application of remote sensing and digital soil mapping tools. The developed method is referred as the e-SOTER approach and is capable of producing a stack of soil diagnostic element layers with the likelihood of their occurrence within each pixel and a layer of WRB reference soil groups (RSG). This new approach may provide better input for modellers and predict the spatial continuum of the soil cover in a much better resolution than the traditional polygon based approaches. At the same time the diagnostic elements, as building blocks of the classification systems, help the correlation of the national soil classes into integrated databases and maps.